Mastoparan M Suppressed NLRP3 Inflammasome Activation by Inhibiting MAPK/NF-κB and Oxidative Stress in Gouty Arthritis - Yunbo Yan; Linqian Yu; Binyang Chen; Chang'an Cao; Hairong Zhao; Qiang Wang; De Xie; Yuemei Xi; Chenggui Zhang; Jidong Cheng (2023)
Background: Gouty arthritis is characterized by the accumulation of monosodium urate crystals (MSU) in the synovial joints and surrounding tissues. Mastoparan M (Mast-M) is a biologically active peptide composed of 14 amino acids, extracted from wasp venom. This study aims to assess the impact of Mast-M on in vitro and in vivo gouty arthritis induced by lipolyaccharide (LPS) plus MSU crystal stimulation. Methods: PMA-differentiated THP-1 macrophages were pre-treated with Mast-M or left untreated, followed by stimulation with LPS and MSU crystals. Cell lysates were collected to assess the expression of the NLRP3 inflammasome, inflammatory signaling pathways, and oxidative stress. Furthermore, to evaluate the in vivo anti-inflammatory effect of Mast-M, an experimental acute gouty arthritis mouse model was established through intra-articular injection of MSU crystals. Results: Mast-M treatment demonstrated significant inhibition of the phosphorylation of MAPKs/NF-κB signaling pathways and reduction in oxidative stress expression in LPS and MSU-induced THP-1 macrophages. This resulted in the suppression of downstream NLRP3 inflammasome activation and IL-1β release. In vivo, Mast-M effectively attenuated the inflammation induced by MSU in mice with gouty arthritis. Specifically, Mast-M reduced swelling in the paws, inhibited the infiltration of neutrophils and macrophages into periarticular tissue, and decreased the activation of the NLRP3 inflammasome and IL-1β production. Conclusion: Mast-M significantly improves gouty arthritis, and its potential mechanism may be achieved by inhibiting the MAPK/NF-κB pathway and alleviating oxidative stress, thus suppressing the activation of NLRP3 inflammasomes. Keywords: Mastoparan M, NLRP3, MAPKs, NF-κB, oxidative stress, gout